Assessment of the Anti-Inflammatory, Antibacterial and Anti-Aging Properties and Possible Use on the Skin of Hydrogels Containing Epilobium angustifolium L. Extracts - Nowak, Anna; Zagórska-Dziok, Martyna; Perużyńska, Magdalena; Cybulska, Krystyna; Kucharska, Edyta; Ossowicz-Rupniewska, Paula; Piotrowska, Katarzyna; Duchnik, Wiktoria; Kucharski, Łukasz; Sulikowski, Tadeusz; Droździk, Marek; Klimowicz, Adam (Frontiers in Pharmacology, 2022)
Epilobium angustifolium L. is an ethnomedicinal plant known as a medicinal plant in many regions of the world, among others, in various skin diseases. Despite the great interest in this plant, there are still few reports of biological activity of ready-made dermatological or cosmetical preparations containing the E. angustifolium extracts. The antioxidant, anti-ageing, anti-inflammatory, antibacterial properties and toxicity, wound healing, and skin permeation of topical hydrogels containing E. angustifolium extracts (HEas) was assessed. First, the plant extracts were prepared using three solvents: 70% (v/v) ethanol, 70% (v/v) isopropanol and water, next by preparing hydrogels witch by dry extracts (HEa-EtOH), (HEa-iPrOH) and (HEa-WA), respectively. Finally, the content of selected phenolic acids in the HEas was evaluated by high-performance liquid chromatography (HPLC). All the HEas were characterized by high antioxidant activity. The most increased antibacterial activity was observed for a strain of Streptococcus pneumoniae ATCC 49619, Escherichia coli, Enterococcus faecalis ATCC 29212, Enterococcus faecium, Sarcina lutea ATCC 9341 and Bacillus pseudomycoides, while the strains of Streptococcus epidermidis, Bacillus subtilis and Staphylococcus aureus were the least sensitive. All the HEas showed a reduction in the activity of lipoxygenase enzymes, proteases, and inhibition of protein denaturation. The HEa-EtOH and HEa-iPrOH also enhanced the wound healing activity of HDF cells. Additionally, in vitro penetration studies were performed using the Franz diffusion cells. These studies showed that the active ingredients contained in E. angustifolium penetrate through human skin and accumulate in it. Furthermore, the hydrogels containing E. angustifolium extracts showed a broad spectrum of activity. Therefore, they can be considered as an interesting alternative for dermatologic and cosmetic preparations.